Typology of how 'harmful commodity industries' interact with local governments in England: a critical interpretive synthesis. Issue 1 (23rd January 2023) - McKevitt, Sarah; White, Martin; Petticrew, Mark; Summerbell, Carolyn; Vasiljevic, Milica; Boyland, Emma; Cummins, Steven; Laverty, Anthony A; Junghans, Cornelia; Millett, Christopher; De Vocht, Frank; Hrobonova, Eva; et al.
Abstract : Introduction: Industries that produce and market potentially harmful commodities or services (eg, tobacco, alcohol, gambling, less healthy foods and beverages) are a major influence on the drivers of behavioural risk factors for non-communicable diseases. The nature and impact of interactions between public bodies and 'harmful commodity industries' (HCIs) has been widely recognised and discussed at national and international levels, but to date little is known about such interactions at local or regional government levels. This study aimed to identify and characterise actual and potential interactions and proposes a typology of interactions between HCIs and English local authorities (LAs). Methods: Five electronic databases covering international literature (PubMed, EBSCO, OVID, Scopus and Web of Science) were searched up to June 2021. We also performed online searches for publicly available, web-based grey literature and documented examples of interactions in an English LA context. We conducted a critical interpretive synthesis of the published and grey literature to integrate and conceptualise the data in the context of English LAs. Results: We included 47 published papers to provide the frame for the typology, which was refined and contextualised for English LAs through the available grey literature. Three categories were developed, describing the medium through which interactions occur: (1) direct involvement with LAs, (2) involvement through intermediaries and (3) involvement through the local knowledge space. Within these, we grouped interactions into 10 themes defining their nature and identified illustrative examples. Conclusion: Our typology identifies complex inter-relationships and characterises interactions between HCIs and LAs, with illustrative examples from English LAs. Drawn from well-established theories and frameworks in combination with contextual information on English LAs, this typology explores the LA perspective and could help local decision-makers to maximise population health while minimising negative impacts of HCIs. PROSPERO registration number: CRD42021257311